British Role in Establishing Modern Legislative System in Kelantan - Arifin, Azmi; Rosdi, Mohamad Roslaily (European Publisher, 2019)
This study discusses the British role in the introduction and formulation of modern law systems in Kelantan in the early 1900s. The objective of this study is to analyze the British role in introducing a modern legal system and its impact on Kelantan in the early 20th century. This research employed historical methods with quantitative and qualitative approaches based on primary and secondary sources. The findings of this study illustrated that there was a significant change in the legal system of Kelantan when the western element began to be injected in the Kelantan legal practice. In fact, in terms of the implementation of Western law, it became significantly dominant after the British dominance of the administrative affairs of the Kelantan government. The restructuring exercise since the early introduction of British law had given new life and renewal to law administration, e.g. criminal law in Kelantan. However, the impact of these changes was found to be completely unacceptable by the indigenous community which had led to the outbreak of several conflicts. The reformation of the state law of Kelantan created a shift between two principal entities in Kelantan's administration namely the Sultanate institutions and British colonial administration, which explained the dilemma and conflict that arose from British initial attempt of intervention in the affairs of the indigenous law in Kelantan.